Soil Organic Carbon: 4/1000 and Land Restoration - Winowiecki, Leigh Ann; Vågen, Tor-Gunnar (2017)
Soil Organic Carbon: 4/1000 and Land Restoration by Leigh Ann Winowiecki, World Agroforestry Centre. Presentation made at Soil Carbon Sequestration: Supporting NDCs and donor action. A CGIAR-wide workshop held 12 Nov 2017 at ZEF Center for Development Research, University of Bonn. Workshop organized jointly by: CGIAR Research Programs on Climate Change, Agriculture and Food Security (CCAFS); Water, Land and Ecosystems (WLE) and Forests, Trees and Agroforestry (FTA).